The Influence Of Content Marketing, Experiential Marketing, And Influencer Marketing On Customer Loyalty Mediated By Customer Engagement (Study On Ms. Glow Products) - Azie Aenun Nazib, M.; Welsa, Henny; Kusuma Ningrum, Nonik (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The rapid development of the internet has changed various aspects of life including consumer behavior such as how to obtain information, the need to make decisions in a fast way without being bound by space and time, and the need for self-actualization in cyberspace. This phenomenon causes traditional marketing such as advertisements through television, newspapers or magazines to be no longer effective because promotional advertisements only contain monotonous promotion of a product or service. Currently, many companies carry out marketing activities for products and services using social media marketing. One company that uses marketing tools through the Instagram social media platform is Ms. Glow. Ms. Glow is a beauty industry. So the purpose of this study is to analyze the effect of Content Marketing, Experiential Marketing and Influencer Marketing on Customer Loyalty mediated by Customer Engagement (Study on Ms. Glow Products). This research is a quantitative study by distributing questionnaires to 150 random respondents who live in Central Java. This research uses non probability sampling category with accidental purposive sampling technique. The results of this study reveal that there is an effect of Content Marketing, Experiential Marketing, Influencer Marketing on Customer Loyalty mediated by Customer Engagement.